2015
DOI: 10.1038/ncomms8149
|View full text |Cite
|
Sign up to set email alerts
|

Wearable red–green–blue quantum dot light-emitting diode array using high-resolution intaglio transfer printing

Abstract: Deformable full-colour light-emitting diodes with ultrafine pixels are essential for wearable electronics, which requires the conformal integration on curvilinear surface as well as retina-like high-definition displays. However, there are remaining challenges in terms of polychromatic configuration, electroluminescence efficiency and/or multidirectional deformability. Here we present ultra-thin, wearable colloidal quantum dot light-emitting diode arrays utilizing the intaglio transfer printing technique, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
331
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 588 publications
(332 citation statements)
references
References 52 publications
1
331
0
Order By: Relevance
“…The upper image above the printed device column for each printing method depicts PL images of the transfer‐printed RGB QD patterns (reprinted from Refs. 110 and 111 with permission), while the lower part shows the transfer efficiencies of a pattern with different sizes, comparing the resolution limitations of both methods (reprinted from Ref. 111 with permission).…”
Section: Patterning and Alignment Methods For Display Applications Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The upper image above the printed device column for each printing method depicts PL images of the transfer‐printed RGB QD patterns (reprinted from Refs. 110 and 111 with permission), while the lower part shows the transfer efficiencies of a pattern with different sizes, comparing the resolution limitations of both methods (reprinted from Ref. 111 with permission).…”
Section: Patterning and Alignment Methods For Display Applications Ofmentioning
confidence: 99%
“…110 and 111 with permission), while the lower part shows the transfer efficiencies of a pattern with different sizes, comparing the resolution limitations of both methods (reprinted from Ref. 111 with permission). b) A full‐color QD active matrix display fabricated by ink‐jet printing.…”
Section: Patterning and Alignment Methods For Display Applications Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of doping strategies have shown both doping polarities in PbS QDs 116 , making it a versatile sensitizing system to combine with any channel material. Solution-processed CQD optoelectronic devices have already demonstrated compatibility with CMOS technology 117,118 and flexible device concepts 119,120 .…”
Section: Ideal Sensitizer Characteristicsmentioning
confidence: 99%
“…For example, one of the recent studies demonstrated the highly deformable wearable QLEDs whose total thickness is less than 3 μm including device parts and double-layered encapsulation layers. 99 More information on ultrathin encapsulation layers for flexible QLEDs is available in the following section on wearable quantum dot displays.…”
Section: Device Structure and Operation Principles Of Qledsmentioning
confidence: 99%